Influences of PbS Quantum Dot Layers on Power Conversion Efficiency of Single Junction GaAs Solar Cells - Lam, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics, 2019)
This paper investigates how PbS coating layers influence the characteristics of GaAs single junction solar cells through I-V characteristic measurements, optical reflectance spectra, and quantum efficiencies. To determine the expected influence, PbS quantum dots were coated on the surface of single junction GaAs solar cells by a drop coating method and the thickness of PbS quantum dot layer was controlled through changing the number of coating layers. The results show that, the short-circuit current can be improved up to 15% with two PbS coating layers. Other parameters such as V oc and FF are hardly affected by the number of PbS coating layers. Based on the results of the optical reflectance spectra and quantum efficiencies, the enhancement in the short-circuit current can be attributed to the antir-eflection of the PbS layers and the ability to transfer high energy photon-generated charge carriers.